Multi‐instrument, high‐resolution imaging of polar cap patch transportation. Issue 9 (25th September 2015) - Thomas, E. G.; Hosokawa, K.; Sakai, J.; Baker, J. B. H.; Ruohoniemi, J. M.; Taguchi, S.; Shiokawa, K.; Otsuka, Y.; Coster, A. J.; St.‐Maurice, J.‐P.; McWilliams, K. A.
Abstract Transionospheric radio signals in the high‐latitude polar cap are susceptible to degradation when encountering sharp electron density gradients associated with discrete plasma structures, or patches. Multi‐instrument measurements of polar cap patches are examined during a geomagnetic storm interval on 22 January 2012. For the first time, we monitor the transportation of patches with high spatial and temporal resolution across the polar cap for 1–2 h using a combination of GPS total electron content (TEC), all‐sky airglow imagers (ASIs), and Super Dual Auroral Radar Network (SuperDARN) HF radar backscatter. Simultaneous measurements from these data sets allow for continuous tracking of patch location, horizontal extent, and velocity despite adverse observational conditions for the primary technique (e.g., sunlit regions in the ASI data). Spatial collocation between patch‐like features in relatively coarse but global GPS TEC measurements and those mapped by high‐resolution ASI data was very good, indicating that GPS TEC can be applied to track patches continuously as they are transported across the polar cap. In contrast to previous observations of cigar‐shaped patches formed under weakly disturbed conditions, the relatively narrow dawn‐dusk extent of patches in the present interval (500–800 km) suggests association with a longitudinally confined plasma source region, such as storm‐enhanced density (SED) plume. SuperDARN observations show that the backscatter power enhancements corresponded to the optical patches, and for the first time we demonstrate that the motion of the optical patches was consistent with background plasma convection velocities.